The Effectiveness of Using Health Education Video on Increasing Knowledge of Household Contacts of Pulmonary Tuberculosis Patients - Nataladi, Evani; Permatasari, Henny; Nursasi, Astuti Yuni; Mulyono, Sigit (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2026)
Despite extensive health education efforts, pulmonary tuberculosis (TB) incidence remains high, particularly among household contacts. Audiovisual media (video) is emerging as a potential alternative to optimize educational outcomes where traditional methods have underperformed. This systematic review evaluates the effectiveness of video-based health education in increasing knowledge and preventive behaviors among household contacts of pulmonary TB patients. A systematic search was conducted (February-March 2025) across five databases: ProQuest, ScienceDirect, Scopus, Sage Journals, and Google Scholar. Using PRISMA guidelines and JBI critical appraisal tools, six high-quality articles were synthesized from an initial 19,481 records (filtered for Open Access, 2016-2025, and relevant study designs). Synthesis of the included studies demonstrates that health education significantly enhances knowledge, attitudes, and participation in early TB detection. Specifically, audiovisual tools were found to improve information retention and understanding of TB prevention more effectively than standard verbal counseling, although its success is often contingent. Audiovisual-based health education is a superior intervention for increasing the knowledge and preventive attitudes of TB household contacts. The integration of video media significantly enhances information uptake compared to traditional methods, suggesting that TB control programs should prioritize digital audiovisual tools to optimize early case detection and community-based prevention.